Growth pattern of Fortunian scalidophoran sclerites - Qin, Jiachen; Liu, Yunhuan; Shao, Tiequan; Liu, Mingjin; Zhang, Yanan (Frontiers in Earth Science, 2023)
Fortunian scalidophoran worms have shown high diversity, with 7 genera and species and 10 indeterminate forms. Current studies have mainly focused on morphology as well as early evolution, and studies on ontogeny have not been carried out due to the limited number of specimens. Here, we report new material of an Orsten-type preserved Indeterminate Form 3 from the Zhangjiagou section. Collected specimens of Indeterminate Form 3 with different annulus widths indicate the presence of several ontogenetic stages. We found newly formed sclerites on the annulus of Indeterminate Form 3 at different ontogenetic stages, suggesting that the sclerites of Indeterminate Form 3 become more numerous in addition to increasing in size during growth. The size of the large sclerites may also increase as the worms grow, however, their number may not change.